Independent Commissioners Moderating the Impact of Green Investment, Carbon Performance, on Carbon Emission Disclosure - Bastri, Amelia; Nursida, Nina (Universitas KH. Abdul Chalim Mojokerto, 2026)
Global Climate Change emerged as a critical issue with extensive ramifications. Indonesia is one of the sixth countries in terms of carbon emissions in the world. Reducing carbon emission is top priority for the Indonesian governance, which is why they’ve passed legislation. But carbon emission disclosure is still not widely used and is often unreliable. The research investigates the association between carbon disclosure, green investment and carbon performance, along with the moderating effect of independent commissioners. This research employs a quantitative methodology utilizing panel data regression on 55 energy sector firms listed on the Indonesia Stock Exchange from 2022 to 2024. The data was analyzed utilizing EViews 13. Green Investment does not significantly impact carbon emission disclosure, whereas carbon performance has significant positives, while independent commissioners do not strengthen the correlation between green investment and disclosure, rather, they enhance the association between carbon performance and carbon emissions disclosure. This discovery highlights the significance of carbon performance and green investment in fostering transparency and the necessity of independent oversight in enhancing disclosure quality